Pengawasan Iklan Pelayanan Kesehatan Tradisional di Televisi - Panuju, Redi (Jurnal Studi Komunikasi, 2017)
Television is a mass communication media that is still in demand by the public to get information and entertainment. Although the era of cyber that grows social media is in sight, but television is the audiovisual media is the easiest convergence so that in the future any television remains connected to social media. Therefore, television will be a priority medium for the industry to market its products or services. Along with that television became the trust of the traditional health care industry to market its products and services. While some of the traditional health care industry is suspected of violating government regulations that prohibit its existence to publish and advertisement.Â The Indonesian Broadcasting Commission has the responsibility and authority to oversee the availability of such advertisements because the law authorises them. But apparently, the supervision is not effective, proven advertising of traditional health services increasingly rampant in television. This is because the KPI does not have the authority to impose sufficient sanctions to broadcasters so as to create a deterrent effect. Besides, it turns out that advertising from traditional health services is the primary income currently for television media, especially local television. The government is also facing a similar dilemma to impose severe sanctions because traditional health services still have a place in society. There needs to be a law-level regulation that can accommodate the problem